The effect of estrogen receptor agonists on pancreaticobiliary duct ligation induced experimental acute pancreatitis - (:unkn) unknown (My University, 2017)
The 17β-estradiol plays a role in physiology of pancreas and may protect it from inflammation. To examine the possible anti-inflammatory effects of 17β-estadiol in pancreaticobiliary duct ligated (PBDL) acute pancreatitis (AP) model, and the underlying mechanism that 17β-estradiol acts on, via evaluating the direct and the receptor related effects by using 17β-estradiol, ER-α and -β agonists. In the study both sexes of rats (n = 88) were used. Animals were divided into two groups as PBDL and PBDL + ovariectomized. ER-α agonist propyl-pyrazole-triol (PPT; 1 mg/kg/day), ER-β agonist diarylpropionitrile (DPN; 1 mg/kg/day) and 17β-estradiol (10 mg/kg/day) were administered to the groups for 3 days following AP induction. On the 3rd day, lung and pancreas tissues and serum samples were taken for malondialdehyde (MDA), glutathione (GSH), myeloperoxidase (MPO), superoxide dismutase (SOD) and interleukin (IL) assays, and histological analyses. In both tissues of male and female AP groups MPO, MDA, SOD levels were increased (P < 0.05 - 0.01) and GSH levels were decreased (P < 0.05). Pancreas and lung MDA and SOD levels were improved with all treatments in female, except lung MDA levels of PPT-treated ones, while lung MDA and SOD levels were improved by PPT and 17β-estradiol in females and via PPT in males (P < 0.05 - 0.001). The increased MPO levels were inhibited with PPT in male pancreas and female lung and with 17β-estradiol in female pancreas (P < 0.05). The increased pro-inflammatory ILs were declined by treatments (P < 0.05 - 0.001). 17β-estradiol and ER-α and -β agonists reduced oxidative pancreatic and pulmonary damage. Estrogen and agonists might have protective role in AP.
Keywords: Female; Animals; Male; Glutathione; Malondialdehyde; Superoxide Dismutase; Peroxidase; Bile Ducts; Ligation; Rats, Sprague-Dawley; Lung; Cytokines; Estradiol; Estrogens; Nitriles; Phenols; Propionates; Pyrazoles; Acute Disease; Pancreas; Pancreatitis; Ovariectomy